Organization Features and Profitability: Implications for a Sample of Emerging Countries - Tariq Tawfeeq Yousif Alabdullah; Essia Ries Ahmed; Ramyar Rzgar Ahmed (Universitas Negeri Malang, 2021)
A huge number of prior works has tested the link between control mechanisms and organization profitability. Several methods are used by such works to enhance the notion that there is an inconsistent result in the link between the board feature and organization profitability. However, there is unpredictability of this link shown by the prior works. Thus, the current work aims at testing the board features as internal control mechanisms represented by the size of both organization and the board of directors in their impact on organization profitability in the non-financial companies in Jordan, which was selected from a sample of Emerging Countries. Data were collected from the annual reports for 65 organizations for the year 2019 from the website of ASE via utilizing a cross-sectional analysis study. After testing the hypothesis of the current work, the findings revealed that the size of the board of director has a significant impact on the organization profitability of nonfinancial companies in Jordan. However, this work showed that organization size has an insignificant impact on organization profitability. The current work might help policymakers in Emerging Countries in general, and Jordanian non-financial sector in particular, deliberate policies related to using robust control mechanisms to enhance directors' commitment toward utilizing internal control mechanisms for the ultimate aim in promoting organization profitability